Simulation of Seepage and Water Tightening Limit in Dam Foundation by Using of Hydro Mechanical Analysis: Upper Gotvand Dam - Sharifzadeh, Mostafa; Nateghi, R.; Kiani, M. (Amirkabir University, 2009)
Seepage and ways of water tightening is one of the fundamental parameters in choosing the situation of large dames. In the field of seepage estimation considering the position of joints because of high capability of fluid flow in comparison to the porosity of the rock is so important. Also fluid of flow in rock mass as a result of changes in aperture of the joints is so impressible of effective stresses exerted on it. In this paper it has been tried to create a 3dimentional model of upper Gotvand dam with capability of hydro mechanical simulation by using of distinct element method, with the results of numerical modeling the water tightening limit was estimated 85 meter and seepage between 3.2 to 16.8 (m3/s).